THE LEGISLATION SCHEME IN TRANSPORTATION OF DANGEROUS GOODS - Babin, Matej (Doprava a spoje, 2012)
The highest priority in process of creation standards in primary legislation has the UN. Important global directive is GHS. For transportation by rail there are two main organizations responsible for creation of changes in Europe for ground transport is UNECE and the OTIF. Transport regime SMGS is related to those countries, which are members of OSJD mainly eastern European and Asia countries.